IMPACT OF INTELLECTUAL CAPITAL, PROFITABILITY AND DIVIDEND ON MARKET CAPITALIZATION - Elfenso, Parcella Glatia; Imelda, Elsa (Graduate Program of Universitas Tarumanagara, 2025)
The purpose of this study is to obtain empirical evidence on the impact of intellectual capital, profitability, and dividends on market capitalization as the dependent variable. The study employs a quantitative approach, using a sample of 66 observations obtained from 22 companies listed in the IDX80 index on the Indonesia Stock Exchange during the period of 2021–2023. The sample was selected using purposive sampling, which allows for data selection based on specific criteria relevant to the research objectives. The statistical software EViews 13 was used for data processing, enabling in-depth analysis using multiple linear regression. The results show that profitability has a significant positive effect on market capitalization, meaning that companies with higher profitability tend to have higher market capitalization. This reflects the importance of strong financial performance in enhancing a company's value in the market. In contrast, intellectual capital and dividends were found to have no significant effect on market capitalization in this sample. These findings offer valuable insights for managers and investors, emphasizing the importance of focusing on profitability to increase a company's appeal in the capital market. This study also encourages further research into other factors that may influence market capitalization.